Prepoznavanje osnovnih prsti slovenske klasifikacije - Repe, Blaž (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
Slovenia does not rank among the important agricultural countries. But recently, we hear more and more about self-supply and self-sufficiency, particularly in relation to all the negative trends from climate changes, fossil fuel prices rising and urban sprawl. All, including geographers, have often problems with soil identification in the field. In this article we will show a simple method of soil type determination according to Slovene soil classification, highlight issues which and where are those natural soils, the most important for food production and local self-sufficiency, and require the highest level of protection, where are restrictions on other natural soil types and how can indicator plants help in soil characteristics determination.
Keywords: pedogeografija; prst (pedologija); Slovenia; Slovenija